The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1523/jneurosci.1834-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Odor Mixtures in the Zebrafish Olfactory Bulb

Abstract: Components of odor mixtures often are not perceived individually, suggesting that neural representations of mixtures are not simple combinations of the representations of the components. We studied odor responses to binary mixtures of amino acids and food extracts at different processing stages in the olfactory bulb (OB) of zebrafish. Odor-evoked input to the OB was measured by imaging Ca 2ϩ signals in afferents to olfactory glomeruli. Activity patterns evoked by mixtures were predictable within narrow limits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
127
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(139 citation statements)
references
References 43 publications
12
127
0
Order By: Relevance
“…We show that a rather fine rearrangement occurs from AL input to output and that such a rearrangement results in a higher separation power between complex odors. Several studies suggested that mixture representation is rather elemental at the input level (zebra fish: Tabor et al 2004;bees: Deisig et al 2006;moths: Carlsson et al 2007; fruit flies : Silbering et al 2007), even though within individual ORNs nonlinear responses to mixtures can be observed (Akers and Getz 1993;Cromarty and Derby 1998;Duchamp-Viret et al 2003). At the output level, studies in the zebrafish (Tabor et al 2004) and in Drosophila (Silbering et al 2007) showed an increased proportion of cases of nonlinear summation between component signals within individual neurons or glomeruli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We show that a rather fine rearrangement occurs from AL input to output and that such a rearrangement results in a higher separation power between complex odors. Several studies suggested that mixture representation is rather elemental at the input level (zebra fish: Tabor et al 2004;bees: Deisig et al 2006;moths: Carlsson et al 2007; fruit flies : Silbering et al 2007), even though within individual ORNs nonlinear responses to mixtures can be observed (Akers and Getz 1993;Cromarty and Derby 1998;Duchamp-Viret et al 2003). At the output level, studies in the zebrafish (Tabor et al 2004) and in Drosophila (Silbering et al 2007) showed an increased proportion of cases of nonlinear summation between component signals within individual neurons or glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…Because natural odors are complex blends including many different components, studying how the neural code for olfactory mixtures is reshaped by AL processing is imperative to understand odor processing in a natural framework. At the OB/AL input level, mixture representation follows essentially elemental rules because it can be predicted from the responses to the components (Carlsson et al 2007; Deisig et al 2006;Silbering and Galizia 2007;Tabor et al 2004). By contrast, at the AL output level, strong interactions between component signals within the AL networks were found in the zebrafish (Tabor et al 2004) and Drosophila (Silbering and Galizia 2007), assigning unique properties to each mixture's representation and making it different from the sum of its components.…”
Section: Introductionmentioning
confidence: 99%
“…1, available at www.jneurosci.org as supplemental material), three (30%) were to two components, and one (10%) was to three components. Finally, to exclude the possibility that the lack of responses to certain mixtures was attributable to cancellation of responses between mutually inhibitory components (Oka et al, 2004;Tabor et al, 2004), the responses of all (n ϭ 44) cells to individual components of a randomly chosen noneffective mixture were also examined. No responses to individual components in noneffective mixtures were found, reinforcing the idea that mitral cells only respond to a very small fraction of odorants in our panel.…”
Section: Mitral Cells In the Mob Exhibit Narrower Responsiveness Thanmentioning
confidence: 99%
“…Glomeruli serve as the site of synaptic contact between olfactory receptor neurons and second-order neurons, mitral/tufted cells. Most naturally occurring odors are complex mixtures, and the spatial pattern of glomerular activity reflects both individual components (Lin et al, 2006) and early intercomponent interactions (Joerges et al, 1997;Vickers et al, 1998;Tabor et al, 2004). In addition to spatial patterns, both glomerular (Spors et al, 2006) and mitral/ tufted cell activity (Meredith, 1986;Cang and Isaacson, 2003) demonstrate stimulus-specific temporal structure.…”
Section: Introductionmentioning
confidence: 99%